Перспективи на хипотекарното кредитирање после глобалната финансиска криза - Велкова, Емилија (Економски факултет, УКИМ, Скопје, 2017)
The U.S. subprime mortgage crisis was one of the first indicators of the subsequent financial crisis, characterized by rise in subprime mortgage delinquencies and foreclosures. A detailed analysis of the causes of the subprime mortgage crisis helps us in the deliberations and the analysis of the possible solutions and lessons learned from the subprime crisis. That further leads toward determination that it is more than needed a new approach to mortgage lending as a proposal for the future development of mortgage lending process in the developed countries. The experiences of the developed countries, as well as the experiences of some of the former socialist countries are very useful and lead toward determination of the starting points for development of the primary mortgage market and the creation of the secondary mortgage market in the Republic of Macedonia in the future.
Perspectives on the mortgage lending after the global financial crisis
Докторска дисертација одбранета во 2017 година на Економскиот факултет во Скопје, под менторство на проф. д–р Михаил Петковски.
Keywords: mortgage market, primary mortgage market, secondary mortgage market, mortgage lending, subprime morgage crisis, new approach to mortgage lending